2013
DOI: 10.1007/s00383-013-3337-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic percutaneous extraperitoneal closure for inguinal hernia: learning curve for attending surgeons and residents

Abstract: Our learning curve analysis showed that whereas attending surgeons needed a mean of 12 operations to perform LPEC repairs safely in 30 min or less, residents needed more than 30 operations to safely perform LPEC repairs without supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Yoshizawa et al also reported the learning curve of LPEC with the conclusion that residents require about 30 operations to perform LPEC safely, which was fewer times than our results [7]. It was because their standard point was 30 min, which was more lenient than our study.…”
Section: Discussionmentioning
confidence: 41%
“…Yoshizawa et al also reported the learning curve of LPEC with the conclusion that residents require about 30 operations to perform LPEC safely, which was fewer times than our results [7]. It was because their standard point was 30 min, which was more lenient than our study.…”
Section: Discussionmentioning
confidence: 41%
“…In spite of this being a relatively new technique to the two surgeons, our excellent results illustrate the ease of learning and mastering our technique. Yoshizawa et al [16] found a similar learning curve using their technique with attending surgeons requiring 12 cases to become proficient and safe.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, there is a trend for increased reports of extraperitoneal closure because of its ease of use and good results [24]. In particular, LPEC, reported by Takehara et al [4], is performed widely in Japan [10,11,[13][14][15]. There have been some comparisons between traditional open herniorrhaphy and laparoscopic repair, including a randomized study and a systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of laparoscopic hernia repair can be divided into two groups. The first group is intraperitoneal internal ring suturing [1][2][3], and the second is extraperitoneal closure [4][5][6][7][8][9][10][11][12][13][14][15]. Recently, there is a trend for increased reports of extraperitoneal closure because of its ease of use and good results.…”
mentioning
confidence: 99%